Chester Barkingham saves the country - Falatko, Julie; Byrne, Eva (Simon & Schuster, 2024)
Moving into the White House when he's adopted by the president's daughter, Chester Barkingham starts sending memos on what they should do when Congress and lawmakers become deadlocked, causing Capitol Hill chaos, in this pawsitive picture book told in presidential memos.
Keywords: Presidents' pets -- United States -- Fiction; Dogs -- Fiction; Picture books; Picture books